The Influence of Industrial-Scale Pack-Boroding Process Time on Thickness and Phase Composition of Selected Cold-Work Tool Steels - Jopek, Jakub; Goral, Marek; Koscielniak, Barbara; Ochal, Kamil; Drajewicz, Marcin; Mokrzycka, Magdalena; Kubaszek, Tadeusz; Dychton, Kamil; Gancarczyk, Kamil; Gradzik, Andrzej; Kwasniewski, Pawel; Gluchowski, Wojciech (Manufacturing Technology Journal, 2023)
The boride coatings are characterized by attractive set of properties such as high hardness and wear resistance, corrosion resistance in higher temperatures and no wettability by liquid metals like alumi-num and zinc. This type of coating might be used for manufacturing of different parts from tool steels. In present article the influence of pack boriding time (2,4,6h) on microstructure and phase composition of obtained coatings is scrutinized. The pack boriding process was conducted on two groups of cold work tool steels: low-Cr content: 145Cr6, 90MnCrV8, 60WCrV8 and high-Cr content: X165CrV12, X153CrMoV12. The commercial boriding pack Ekabor 2 was utilized and the process was carried out using industrial CVD device (Bernex BPX Pro 325S). The conducted research showed that the boride coatings formed on the substrate of high-chromium steels were characterized by a lower total thick-ness. On low-chromium steels, FeB phase was discontinuous as an irregular islands located in the near-surface area. On the other hand, for high-chromium steels, a continuous layer of needle-like borides was formed.
Keywords: Boride coatings; Pack boriding; FeB; Fe2B; Tool steel